2009
DOI: 10.1021/nl803205c
|View full text |Cite
|
Sign up to set email alerts
|

Protected Peptide Nanoparticles: Experiments and Brownian Dynamics Simulations of the Energetics of Assembly

Abstract: Soluble peptides, susceptible to degradation and clearance in therapeutic applications, have been formulated into protected nanoparticles for the first time through the process of kinetically controlled, block copolymer directed rapid precipitation using Flash NanoPrecipitation. Complementary Brownian dynamics simulations qualitatively model the nanoparticle formation process. The simulations corroborate the hypothesis that the size of nanoparticles decreases with increasing supersaturation. Additionally, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 17 publications
(35 reference statements)
0
34
0
Order By: Relevance
“…1 One solution to this problem is to use amphiphilic block copolymer micelles as "containers" to carry such molecules. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The hydrophilic block forms a corona that sterically stabilizes the particles. In order to be useful, such particles must be sufficiently small (50-400 nm in diameter) and biocompatible.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 One solution to this problem is to use amphiphilic block copolymer micelles as "containers" to carry such molecules. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The hydrophilic block forms a corona that sterically stabilizes the particles. In order to be useful, such particles must be sufficiently small (50-400 nm in diameter) and biocompatible.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these studies focused on systems in which no solvent is present at all (i.e., nanoparticle-polymer composites), [26][27][28][29][30][31] whereas others investigated the formation of polymer-protected nanoparticles in solvent. 12,[32][33][34][35] Most of the latter were either carried out under conditions in which the polymer/solute/nanoparticle concentrations were substantially higher than those encountered in the flash nanoprecipitation process (ppm), or they did not employ a methodology that simulated the dynamic evolution of the system. For example, Chen et al 33 used dissipative particle dynamics (DPD) to study a system containing solvent, diblock copolymers, and hydrophobic solutes, but the lowest solute and copolymer volume fractions studied were 10% and 5%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using Brownian dynamics simulations [24,25], it has been shown that during the FNP process organic particles aggregate with each other or onto the hydrophobic block (A-block) of the copolymer, while the hydrophilic block (B-block) of the copolymer stretches in the non-solvent to stabilize the resulting nanoparticles. As the resulting copolymer-organic particle aggregates form micelles, organic protected nanoparticles are formed in the interior of the micelles and further growth is arrested.…”
Section: Introductionmentioning
confidence: 99%